Teaching Western American literature - Harrison, Brady, 1963-; Tanglen, Randi Lynn (Lincoln : University of Nebraska Press, 2020)
"'Teaching Western American Literature' gives instructors a glimpse into the classrooms, syllabi, and assignments of leading scholars in the field"--
7. Moving Beyond the Traditional Classroom and So Far from God -- 8. Quotidian Wests -- 9. Western Writers in the Field -- 10. Placing the Pacific Northwest on the Literary Map -- Part 4 -- 11. National, Transnational, and Human Rights Frames for Teaching María Amparo Ruiz de Burton's The Squatter and the Don -- 12. Able-Bodies, Difference, and Citizenship in the West -- 13. Teaching Western Canadian Literature in the Croatian Context -- Contributors -- Index
Includes bibliographical references and index.
JSTOR
Keywords: Western stories -- Study and teaching; American literature -- Study and teaching; West (U.S.) -- In literature -- Study and teaching; Littérature américaine -- Étude et enseignement; États-Unis (Ouest) -- Dans la littérature -- Étude et enseignement; LITERARY CRITICISM / American / General; American literature -- Study and teaching; West United States; Electronic book